Faecalibacterium prausnitzii: A Next-Generation Probiotic in Gut Disease Improvement - Xiaoya He; Shuyang Zhao; Yan Li (Canadian Journal of Infectious Diseases and Medical Microbiology)
The researchers are paying more attention to the role of gut commensal bacteria in health development beyond the classical pathogens. It has been widely demonstrated that dysbiosis, which means the alternations of the gut microbial structure, is closely associated with development of intestinal chronic inflammation-related diseases such as inflammatory bowel disease (IBD), and even infectious diseases including bacterial and viral infection. Thus, for reshaping ecological balance, a growing body of the literatures have proposed numerous strategies to modulate the structure of the gut microbiota, which provide more revelation for amelioration of these inflammation or infection-related diseases. While the ameliorative effects of traditional probiotics seem negligeable, emerging next generation probiotics (NGPs) start to receive great attention as new preventive and therapeutic tools. Encouragingly, within the last decade, the intestinal symbiotic bacterium Faecalibacterium prausnitzii has emerged as the “sentinel of the gut,” with multifunction of anti-inflammation, gut barrier enhancement, and butyrate production. A lower abundance of F. prausnitzii has been shown in IBD, Clostridium difficile infection (CDI), and virus infection such as COVID-19. It is reported that intervention with higher richness of F. prausnitzii through dietary modulation, fecal microbiota transplantation, or culture strategy can protect the mice or the subjects from inflammatory diseases. Therefore, F. prausnitzii may have potential ability to reduce microbial translocation and inflammation, preventing occurrences of gastrointestinal comorbidities especially in COVID-19 patients.